Improved method and test strategy for recovery of enteric viruses from shellfish. - Metcalf, T G (1980)
An improved recovery method and testing strategy were devised for recovery of low numbers of enteric viruses from each of three commercially important shellfish species. Effective recovery of virus depended as much upon details of the test strategy adopted for use of the improved method with each species as on the method itself. The most important test details involved sample composition, pool size, and method of use of cell cultures. Recovery sensitivity measured permitted detection of 25 to 3 plaque-forming units of enteroviruses and 100 to 27 plaque-forming units of reovirus through their recovery in cell culture, with effectivenesses averaging 64 and 46%, respectively. Test samples prepared by the improved recovery method were virtually cytotoxicity free. Optimal recovery of virus on 45-cm2 cell culture monolayers was obtained with 1-ml inocula adsorbed for 2 h. The most effective recovery of virus from shellfish samples was made by a sequential adsorption procedure which allowed equal exposure of an entire sample to each of two or more cell cultures. Removal of nonviral contaminants from test samples by antibiotic treatment was preferable to the use of ether or membrane filtration procedures.